(untitled) (Research, Society and Development, 2022)
Information Science and Marketing are sciences that have interdisciplinary characteristics that dialogue with each other. Based on this context, this article aims to propose a model of alignment between the practice and academic research of the role of the Information Science professional in the trending informational market and between the practice and academic research of Marketing 5.0. In order to meet this objective, the two subjects under study were initially analyzed, verifying the potential of Marketing 5.0 to be a way of acting in the informational market of trends. Next, an alignment model between apparently different areas was analyzed and adapted to propose interconnections between professional practice and academic research on the two topics in question. The model made it possible to propose a set of interconnections between practice and academic research on the performance of the Information Science professional in the informational market of trends with the practice and academic research of Marketing 5.0. From the study carried out, it was verified the coherence between the interconnections generated between the two areas and, as a result, the potential that the model has for the promotion of new research involving the informational market of trends, considering the performance of the Science professional of Information in Marketing 5.0.